2020
DOI: 10.1007/s10841-020-00229-z
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation composition and structure are important predictors of oviposition site selection in an alpine butterfly, the Mountain Ringlet Erebia epiphron

Abstract: Knowledge of species' ecological requirements is key for designing effective conservation management. In butterflies, the needs of larval stages are often the most specialised part of 2 the life cycle, but for many species information on this is lacking. The Mountain Ringlet Erebia epiphron is a cold-adapted butterfly found in alpine grasslands in mountainous regions of Europe. Efforts to devise conservation strategies for this climate changethreatened species are hampered due to its basic ecology being poorly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Other studies found similar results and draw a connection to the grazing regime at the sites. For the butterfly species Erebia epiphron, the Mountain Ringlet, Ewing et al (2020) found that the quantity of leaf litter influenced egg site selection. Females preferred sites with an intermediate amount of litter.…”
Section: Environmental Variablesmentioning
confidence: 99%
See 4 more Smart Citations
“…Other studies found similar results and draw a connection to the grazing regime at the sites. For the butterfly species Erebia epiphron, the Mountain Ringlet, Ewing et al (2020) found that the quantity of leaf litter influenced egg site selection. Females preferred sites with an intermediate amount of litter.…”
Section: Environmental Variablesmentioning
confidence: 99%
“…Females preferred sites with an intermediate amount of litter. The cover of litter is supposed to function as a microclimatic buffer that reduces temperature and humidity fluctuations and protects hibernating larvae from cold temperatures in winter (Stuhldreher and Fartmann 2014;Münsch et al 2018;Ewing et al 2020). Cold temperatures probably had no influence on the survival of the larvae of C. myrmidone in September, still it might be advantageous for their hibernation.…”
Section: Environmental Variablesmentioning
confidence: 99%
See 3 more Smart Citations